Reimagining Sustainable Organization Perspectives on Arts, Design, Leadership, Knowledge and Project Management - Jevnaker, Birgit Helene; Olaisen, Johan (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"The book gives an excellent understanding of a reimagination and recreation of leadership and organisational theory. Jevnaker and Olaisen present new perspectives and represent a new school of modernity and futurism." - Professor Jon-Arild Johannessen, Kristiania University College and Nord University "Sustainable organizations are becoming imperative in contemporary business, and I highly recommend this book to any reader interested in understanding the fundamental dynamics." - Professor Georg von Krogh, ETH Zurich This open access book reimagines a deeper sustainability in dynamic organization. Offering multiple perspectives on arts, design thinking, leadership, knowledge and project management, Reimagining Sustainable Organization addresses our need for thinking and coping differently when facing the many unknowns of real-life enterprises in society. Drawing on process philosophy, real-world case studies, and examinations of business practices as well as management research, the authors explore knowledge creation towards reimagining sustainable organization. The book includes frameworks and conceptual tools as well as insights for further explorations. This book will be of interests to students, scholars and teachers, and practitioners who are studying sustainable organization, greener management, leadership ideas, or knowledge and project management. It covers future pressing issues also for the professionals involved in co-creative work across organizational boundaries. Birgit Helene Jevnaker is Professor of Innovation and Economic Organization at BI Norwegian Business School, Norway. Her research focuses on strategic sustainable design, entrepreneurship, innovation and collaboration, organization development, arts, knowledge and learning, and leadership in action. Johan Olaisen is Professor in Information and Knowledge Management at BI Norwegian Business School, Norway. His research focuses on information and knowledge management, philosophy of science and research, corporations and organizational change, leadership and project management. .